(untitled) (Biological Sciences - PJSIR, 2022)
A study was carried out to see the blood lead and cadmium levels in fifty employees working at PCSIR Laboratories Complex, Karachi. These employees belonged to various socio-economic groups and had their residences in different areas of Karachi. Sixty two percent staff had blood lead level between 100-200 IlgJL. The highest blood lead level (>4qO IlgJL) was found in volunteers working as garage staff. No significant difference was found between the·blood lead Ie els of volunteers belonging to different socio-economic and age groups. Only 8% or’the staff had blood lead Ie els’below 100 IlgJL. Lead in the dust collected from the residences of the volunteers was also estimated for lead and correlated with blood lead levels. Blood cadmium levels were also estimated. These were found to be higher in smokers and tobacco chewers. A definite correlation was observed between blood cadmium levels and smoking habits.